(untitled) (Research, Society and Development, 2020)
The sediment deposition on water bodies, provided by accelerated erosive processes, is one of the most relevant superficials water’s quality problems of the rio Doce watershed. The erosion can be caused by different ways, among them is rainfall erosion, which can be accentuated by the characteristics of rainfall intensity, slope, and soil type. Aim to characterize the erosive potential of rains in each rio Doce basin cities of Minas Gerais, this paper uses the netErosividade MG software. For this purpose, were selected 190 (hundred ninety) cities of Minas Gerais in the Rio Doce watershed and take their rainfall erosivity values. The data were tabulated through the respective Water Resources Management Unit and organized in a descending way. The output obtained showed that the Piranga unit has the most erosive potential, with 6928,61 , a medium grade. The other two major potentials were the Piracicaba unit (6761,94) and Manhuaçu unit (5884,3), which are also medium grade potential. A sub-basin with the lowest potential output was the Suaçuí, with values ​​of low erosive grade potential, 3417,59 . From the data generated, it was possible to draw a distribution chart of erosive potential over a hydrological year for each sub-basin. Through these results, it is expected that tables, charts, and web map produced may support the actors of water resources management to make public policy decisions at the Rio Doce basin.